Relative age effect in elite Brazilian athletes in different combat sports: an observational study - de Almeida-Neto, P. F.; Neto, R. B.; Medeiros, I.; de Oliveira, F. C. S.; de Oliveira Filho, A. G.; de Matos, D. G.; Dantas, P. M. S.; de Araújo Tinôco Cabral, B. G. (Sport Sciences for Health, 2023)
Background The relative age effect (RAE) suggests that, due to maturity, young athletes born in the first quartiles of the year may have advantages over those born in the last quartiles of the year. Thus, it is important to evaluate the RAE in different sports and to consider the particularities of the subdivisions of the sports categories.